Recommendation and Students’ Authoring in Repositories of Learning Objects: A Case-Based Reasoning Approach - Gomez-Albarran, Mercedes; Jimenez-Diaz, Guillermo (International Journal of Emerging Technologies in Learning (iJET), 2009)
This paper presents a Case-Based Reasoning approach for the personalized recommendation and the studentsâ?? authoring tasks in on-line repositories of Learning Objects (LOs). The recommender combines content-based filtering techniques together with collaborative filtering mechanisms. Studentsâ?? authoring tasks include the incorporation of ratings of the existing LOs and new LOs, which are peer reviewed. This approach is going to be applied to a repository with more than 200 programming examples written in different programming languages.